Ichnogenus Trypanites in the Ordovician of Estonia (Baltica) - Ursula Toom; Jukka Kuva; Dirk Knaust (Estonian Journal of Earth Sciences, 2023)
Trypanites is a common boring in Ordovician hardgrounds of Estonia (Baltica). The depth of the sedimentary basin and sedimentation rates controlled the distribution of Trypanites. The trace-makersâ community was diverse and changing over time. Three ichnospecies of Trypanites can be distinguished: T. sozialis, T. weisei and Trypanites isp. All three morphotypes can be recognized in the same hardground. It is impossible to distinguish between the different ichnospecies based only on the size of the boring aperture. The depth of early lithification of the seafloor determines the morphological variability seen in T. sozialis. The occurrence of elongated borings, such as T. weisei and Trypanites isp., is related to tropical environments, and their trace-makers strongly preferred substrates with a homogeneous and dense texture. The texture and available volume of hard substrate controls the ichnodiversity of Trypanites ichnospecies.